Innate Immune Responses and P. falciparum CS Repeat-Specific Neutralizing Antibodies Following Vaccination by Skin Scarification - Mitchell, Robert A.; Altszuler, Rita; Gonzalez, Sandra; Johnson, Roshawn; Frevert, Ute; Nardin, Elizabeth (Frontiers in Immunology, 2022)
The skin is the site of host invasion by the mosquito-borne Plasmodium parasite, which caused an estimated 229 million infections and 409,000 deaths in 2019 according to WHO World Malaria report 2020. In our previous studies, we have shown that skin scarification (SS) with a P. falciparum circumsporozoite (CS) peptide in the oil-in-water adjuvant AddaVax containing a combination of TLR 7/8 and TLR 9 agonists can elicit sporozoite neutralizing antibodies. SS with AddaVax + TLR agonists, but not AddaVax alone, elicited CD4+ Th1 cells and IgG2a/c anti-repeat antibody. To explore the innate immune responses that may contribute to development of adaptive immunity following SS, we examined the skin at 4h and 24h post priming with CS peptide in AddaVax with or without TLR agonists. H&E stained and IHC-labeled dorsal skin sections obtained 24h post SS demonstrated a marked difference in the pattern of infiltration with F4/80+, CD11b+ and Ly6G+ cells at the immunization site, with the lowest intensity noted following SS with AddaVax + TLR agonists. Serum collected at 4h post SS, had reproducible increases in IL-6, MIP-3α, IL-22 and IP-10 (CXCL10) following SS with AddaVax + TLR agonists, but not with AddaVax alone. To begin to decipher the complex roles of these pro-inflammatory cytokines/chemokines, we utilized IP-10 deficient (IP-10 -/-) mice to examine the role of this chemokine in the development of anti-repeat antibody response following SS. In the absence of IP-10, the levels of Th1-type IgG2a/c antibody and kinetics of the primary anti-repeat antibody response were reduced following prime and boost. The IP-10 chemokine, present as early as 4h post prime, may provide an early serological marker for rapid screening of adjuvant formulations and delivery platforms to optimize SS-induced humoral immunity to CS repeats as well as other pathogens.